ORGANISATIONAL COMMITMENT AND CITIZENSHIP BEHAVIOUR: TOOLS TO IMPROVE EMPLOYEE PERFORMANCE; AN INTERNAL MARKETING APPROACH - Asiedu, Michael; Sarfo, Jacob Owusu; Adjei, Daniel (European Scientific Journal, ESJ, 2014)
The aim of the study is to assess how organisational commitment and organisational (OCB) citizenship impacts on employee performance in the banking industry. The research was a non-experimental, explorative, quantitative study. Structured questionnaire was used to collect data from a sample of two hundred (200) employees from 10 different commercial banks in Ghana to assess whether their performance was influence by their commitment and citizenship behaviour. The results revealed that there is a positive correlation between organisational commitment and organisational citizenship (r = .910**, Ï â‰¤ 0.01). In addition, it was found that organisational commitment (Î² =0.406, t=2.493, P = 0.030 < 0.05), when added to organisational citizenship (Î² =0.589 t=6.216, P = 0.000 < 0.05) produced a greater Î”R2, that is 0.891** as compared to their impact individually. In conclusion, the study result suggests that banks in Ghana can better influence and improve employee performance by combining organisational commitment and organisational citizenship behaviour as internal marketing tools. In addition, the firms should concentrate more efforts on building OCB in employees, if they are to improve performance significantly.